Increasing the psychophysical state of children of primary school age by means of stretching with wushu elements - Korichko, A.V.; Rotar, A.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to improvement of the psychophysical state of children of primary school age by means of stretching with wushu elements. Methods and structure of the study. Children 9-10 years old took part in the pedagogical experiment. The initial level of physical fitness, the degree of workability and mental stability of children of primary school age were preliminarily determined, the features of their psycho-emotional state were revealed. In the course of the study, a program was developed based on the integration of elements of stretching and wushu. To prevent adverse effects on the health of younger schoolchildren (development of asymmetry in the sagittal plane, muscle imbalance), all developed complexes were designed for "mirror" stretching of all departments of the musculoskeletal system. Results and conclusions. The use of stretching with wushu elements in the system of physical education of children of primary school age has a positive effect on the level of physical fitness, as evidenced by the positive dynamics in most of the proposed tests. The positive influence of stretching with wushu elements on the working capacity of those involved was traced. An increase in the efficiency of work and mental stability of children aged 9-10 was noted, which undoubtedly has a positive effect on the quality of classes.